New Age Insights: Filipino Millennials in Government - Chua, Mark Kevin C.; Labid, Sherrie Ann C.; Bolante, Lovely Rose A. (Makara Human Behavior Studies in Asia, 2023)
Millennials comprise a significant portion of the demography of the current Philippine workforce. Cognizant of the unique socio-cultural environment that shaped the Generation Y cohort, this descriptive phenomenological qualitative study aimed to explore millennial employees' work expectations and experiences within a government agency in the Philippines. Four themes emerged from the in-depth analysis of the five employees' interview responses: (1) job security and financial stability, (2) socio-emotional support, (3) fulfillment, and (4) professional development opportunities. The qualitative findings of this study emphasize the importance of supporting millennial employees' career growth and fostering a healthy work environment. It indicates that millennial employees know their value in government service and recognize that job security substantially impacts their performance. The findings of this study provide valuable insights into the work expectations and experiences of millennial employees in a government agency, highlighting the need for institutions to understand and adapt to the unique needs of this generation to foster a productive and engaged workforce.